2016
DOI: 10.17159/2309-8775/2016/v58n1a1
|View full text |Cite
|
Sign up to set email alerts
|

Are estimates of catchment response time inconsistent as used in current flood hydrology practice in South Africa?

Abstract: Catchment response time parameters are one of the primary inputs required when design floods, especially in ungauged catchments, need to be estimated. The time of concentration (TC) is the most frequently used time parameter in flood hydrology practice, and continues to find application in both event-based methods and continuous hydrological models. Despite the widespread use of the TC, a unique working definition and equation(s) are currently lacking in South Africa. This paper presents the results of the dir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 11 publications
1
14
0
Order By: Relevance
“…However, both these equations were developed and calibrated in the United States of America (USA) for catchment areas less than 4 ha and 45 ha respectively (McCuen et al 1984). Gericke and Smithers (2014;2016a;2016b) highlighted the inherent limitations and inconsistencies introduced when these T C equations, which are currently recommended for general practice in South Africa, are applied outside their bounds, both in terms of areal extent and their original regions of development, without using any local correction factors. In a recent study, Gericke and Smithers (2016b;2017) used observed catchment response time parameters to derive new empirical time parameter equations for medium to large catchments in South Africa.…”
Section: O J Gerickementioning
confidence: 99%
“…However, both these equations were developed and calibrated in the United States of America (USA) for catchment areas less than 4 ha and 45 ha respectively (McCuen et al 1984). Gericke and Smithers (2014;2016a;2016b) highlighted the inherent limitations and inconsistencies introduced when these T C equations, which are currently recommended for general practice in South Africa, are applied outside their bounds, both in terms of areal extent and their original regions of development, without using any local correction factors. In a recent study, Gericke and Smithers (2016b;2017) used observed catchment response time parameters to derive new empirical time parameter equations for medium to large catchments in South Africa.…”
Section: O J Gerickementioning
confidence: 99%
“…Design flood events have a specific magnitude-frequency relationship in each location and a sensitivity to the values of the time parameters (Gericke and Smithers 2016). Researchers argue that 75% of the total error in peak discharge can be attributed to errors in estimating time parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers argue that 75% of the total error in peak discharge can be attributed to errors in estimating time parameters. Gericke and Smithers (2016) point out that these errors could not only result in design above or below the hydraulic design of structures but also several socioeconomic implications and unviable projects. Thus, watershed response time parameters should be considered as one of the main inputs needed for floods projections.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On this basis, the existence of numerous equations might become a hindrance when it comes to deciding which is best for a given area, especially when the person using a particular equation is not familiar with how it was derived and/or its advantages and intrinsic limitations. Various studies [1,2,[5][6][7][8][28][29][30][31][32][33][34][35][36] performed in different locations around the world have resulted in large differences among the Tc values estimated by means of multiple equations, which contributes to (a) highlighting the need for assessing the performance of existing Tc equations prior to their use, (b) realizing that the equations cannot be randomly used, and (c) understanding and quantifying the impact on the subsequent computation of the design runoff.…”
Section: Introductionmentioning
confidence: 99%